2007
DOI: 10.1677/joe-07-0248
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans LET-767 is able to metabolize androgens and estrogens and likely shares common ancestor with human types 3 and 12 17β-hydroxysteroid dehydrogenases

Abstract: Mutations that inactivate LET-767 are shown to affect growth, reproduction, and development in Caenorhabditis elegans. Sequence analysis indicates that LET-767 shares the highest homology with human types 3 and 12 17b-hydroxysteroid dehydrogenases (17b-HSD3 and 12). Using LET-767 transiently transfected into human embryonic kidney-293 cells, we have found that the enzyme catalyzes the transformation of both 4-androstenedione into testosterone and estrone into estradiol, similar to that of mouse 17b-HSD12 but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…We could not exclude that, in addition to 3-ketoacyl-CoA reductase activity, LET-767 might also be involved in another activity (e.g. production of steroids proposed earlier (18,19)), which, however, does not lead to the developmental arrest caused by depletion of LET-767, because addition of fatty acids is sufficient to overcome it.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We could not exclude that, in addition to 3-ketoacyl-CoA reductase activity, LET-767 might also be involved in another activity (e.g. production of steroids proposed earlier (18,19)), which, however, does not lead to the developmental arrest caused by depletion of LET-767, because addition of fatty acids is sufficient to overcome it.…”
Section: Discussionmentioning
confidence: 96%
“…5D). It was previously suggested that LET-767 might produce steroid hormones, such as testosterone (19). To check whether steroids might also be important for let-767 (RNAi) developmental arrest, we supplemented the worms with testosterone alone or in combination with fatty acids.…”
Section: Mass Spectrometric Quantification Revealed Altered Fatty Acimentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, high affinity binding for E2 is found in vertebrate ERs, rat and mouse alpha-fetoprotein and sex steroid binding globulin [13], as well as in enzymes in yeast [51], which do not have steroid receptors. Another example of convergence is the presence of over ten 17 -hydroxysteroid dehydrogenases that metabolize estrogens and androgens [13][14]52]. …”
Section: Divergent Evolution Convergent Evolution Horizontal Transfer?mentioning
confidence: 99%
“…17 -HSD12 catalyzes the transformation of both androgens and estrogens Liu et al, 2007). Caenorhabditis elegans LET-767 is known to metabolize androgens and estrogens, and the gene appears to share a common ancestor with human types 17 -HSD3 and HSD12 (Desnoyers et al, 2007). High levels of expression of 17 -HSD1 have been shown to be associated with poor prognosis in breast cancer and late relapse among patients with ER-positive breast tumors (Sasaki et al, 2010;Jansson et al, 2009).…”
Section: β-Hydroxysteroid Dehydrogenasesmentioning
confidence: 99%